Pola Komunikasi Pemerintah Desa dalam Menciptakan Kesadaran Masyarakat Akan Protokol Kesehatan pada Masa Pandemi Covid-19 di Desa Sei Kasih Kecamatan Bilah Hilir Kabupaten Labuhanbatu - Pertiwi Pertiwi; Maraimbang Daulay; Yusra Dewi Siregar (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This study aims to determine the communication pattern of the village government in creating public awareness of health protocols during the Covid-19 pandemic and the obstacles of the village government in creating public awareness of health protocols during the Covid-19 pandemic. The theory used in this research is communication theory and OR theory. The subjects of this study were heads and employees of village government offices. The location of this research was carried out at the Sei Kasih Village office, Bilah Hilir District, Labuhanbatu Regency starting from July - September 2021. The method used in this study was a qualitative method. The analysis technique used is descriptive qualitative. The results of this study are that the communication pattern of the Sei Kasih village government in creating public awareness of health protocols during the pandemic uses primary and secondary communication patterns, and the constraints of the village government in creating public awareness of health protocols during the pandemic are that not all people are always in place at the time of the pandemic. the process of delivering information, it is difficult for people to take the time to listen to information then some people still do not believe that the corona virus in this case is the lack of people to comply with health protocols during the Covid-19 pandemic.